2012
DOI: 10.1515/cclm-2011-0495
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific thyroid hormone and thyrotropin reference intervals for a pediatric and adolescent population

Abstract: AbstractEstablishment of reliable reference intervals remains valuable for confirming validity and advancing standardization across methods and populations. Moreover, knowledge of the measurement uncertainty (U) and of the reference change value (RCV) has important applications in clinical chemistry.Starting from the information available in the laboratory data base (29,901 subjects) an initial selection was carried out by eliminating all subjects with a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 14 publications
2
20
1
3
Order By: Relevance
“…Dynamic changes in thyroid function occur following delivery in the newborn infant, but a serum TSH concentration >5 mU/l can be considered to be abnormal after 1 month of age when modern third-generation assays are used [111,112]. Thereafter, both the serum TSH and thyroid hormone levels continue to decline gradually to values more typical of the adult.…”
Section: Sch In Childhoodmentioning
confidence: 99%
“…Dynamic changes in thyroid function occur following delivery in the newborn infant, but a serum TSH concentration >5 mU/l can be considered to be abnormal after 1 month of age when modern third-generation assays are used [111,112]. Thereafter, both the serum TSH and thyroid hormone levels continue to decline gradually to values more typical of the adult.…”
Section: Sch In Childhoodmentioning
confidence: 99%
“…By contrast, the lower reference values for TSH were more consistent across the studies. Interestingly, Chaler et al ,8 Kratzsch et al ,10 Marwaha et al ,11 Iwaku et al 13 and their colleagues reported a rise in the lower reference values in children aged between 1 and 12 years that is not seen in the other studies.…”
Section: Discussionmentioning
confidence: 86%
“…Chaler et al 8 reported considerably higher upper reference values for FT4 in children aged >2 years using indirect sampling approach of outpatients measured by Abbott AxSYM analyser. By contrast, the upper reference values of FT4 that were derived from direct sampling approach were lower when measured by Abbott Architect analyzers 12 14 17 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations